Adaptive sliding-mode attitude control for autonomous underwater vehicles with input nonlinearities. (1st September 2016) - Cui, Rongxin; Zhang, Xin; Cui, Dong
Abstract: In this paper, we consider attitude control for autonomous underwater vehicles (AUVs) with input nonlinearities and unknown disturbances taken into account. The dynamics model in the 3D space of an AUV is simplified to a second-order dynamics with unknown model parameters and disturbances for the yaw and pitch control. Based on this simplification, a sliding-mode-based adaptive control is proposed for the case without any input nonlinearities. For the dead-zone nonlinearity and unknown disturbances, a sliding-mode-based adaptive control combined with a nonlinear disturbance observer is employed, in which the non-symmetric dead-zone with unknown parameters is modeled as a time-varying disturbance-like term rather than constructing a smooth dead-zone inverse. For rudder saturation, the control is further designed by introducing an auxiliary dynamic compensator. The mathematical proof of the proposed algorithms is presented. Extensive simulation results are presented to illustrate the effectiveness of the proposed control. In addition, experimental results on an AUV whose attitude is controlled by cross-type rudders are also provided to show the effectiveness of the proposed algorithms. Abstract : Highlights: Attitude control design for autonomous underwater vehicles (AUV) is presented, with the model uncertainties, disturbances and input nonlinearities taken into account. A disturbance observer is involved to address the input dead-zone problem and an auxiliary dynamic compensation is proposed for the rudder saturation. The unknown nonlinearities and disturbances are addressed by using the adaptive slide model control.